STUDENTS’ MATHEMATICAL COMMUNICATION SKILLS IN SOLVING DATA PRESENTATION PROBLEMS - Arjuna Yahdil Fauza Rambe; Rama Nida Siregar; Mariam Nasution; Suparni (EMTEKA: Jurnal Pendidikan Matematika, 2026)
Mathematical communication skills are an essential competency in mathematics learning because they help students organize information, represent data, and communicate ideas and problem-solving processes accurately. However, in data presentation topics, students still encounter difficulties in explaining solution procedures, creating visual representations, and using mathematical expressions correctly. This study aimed to analyze students' mathematical communication skills in solving data presentation problems based on the indicators of written text, drawing, and mathematical expression. This research employed a qualitative descriptive approach. The subjects were seventh-grade students of MTs Mamba’ul ‘Ulum, selected based on high, moderate, and low levels of mathematical communication skills. Data were collected through essay tests and semi-structured interviews and were analyzed using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The results showed that students in the high category were able to identify information, present data in tables and diagrams, and use mathematical expressions systematically and accurately. Students in the moderate category were able to communicate mathematical ideas fairly well, although they still made errors in representations and calculations. Meanwhile, students in the low category experienced difficulties in explaining procedures, presenting data visually, and constructing appropriate mathematical models. These findings indicate differences in mathematical communication skills across student categories, which influence the quality of mathematical problem-solving. Kemampuan komunikasi matematis merupakan kompetensi penting dalam pembelajaran matematika karena membantu siswa mengorganisasi informasi, merepresentasikan data, serta mengomunikasikan ide dan proses penyelesaian masalah secara tepat. Namun, pada materi penyajian data masih ditemukan siswa yang mengalami kesulitan dalam menjelaskan langkah penyelesaian, membuat representasi visual, dan menggunakan ekspresi matematis secara benar. Penelitian ini bertujuan untuk menganalisis kemampuan komunikasi matematis siswa dalam menyelesaikan soal penyajian data berdasarkan indikator written text, drawing, dan mathematical expression. Penelitian menggunakan pendekatan deskriptif kualitatif. Subjek penelitian adalah siswa kelas VII MTs Mamba’ul ‘Ulum yang dipilih berdasarkan kategori kemampuan komunikasi matematis tinggi, sedang, dan rendah. Data dikumpulkan melalui tes uraian dan wawancara semi-terstruktur, kemudian dianalisis menggunakan model Miles dan Huberman yang meliputi reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa siswa kategori tinggi mampu mengidentifikasi informasi, menyajikan data dalam bentuk tabel dan diagram, serta menggunakan ekspresi matematis secara sistematis dan tepat. Siswa kategori sedang mampu mengomunikasikan ide matematika dengan cukup baik, meskipun masih melakukan kesalahan pada representasi dan perhitungan. Sementara itu, siswa kategori rendah mengalami kesulitan dalam menjelaskan prosedur, menyajikan data secara visual, dan menyusun model matematika. Temuan ini menunjukkan adanya perbedaan kemampuan komunikasi matematis yang memengaruhi kualitas pemecahan masalah matematika.